PEMBENTUKAN KALUS TANAMAN ROSELLA (Hibiscus sabdariffa) PADA PEMBERIAN NAFTALEN ACETYL ACID (NAA) DAN BENZYL AMINO PURIN (BAP) SEBAGAI SUMBER BELAJAR KONSEP BIOTEKNOLOGI - Imam Mahadi '; Sri Wulandari '; Addarwida Omar ' (Program Studi Pendidikan Biologi, 2014)
Has conducted research for a hand out submateri biotechnology high school students basedon plant tissue culture research Roselle (Hibiscus sabdariffa). The study includes two phases,namely: (1) Experiments to produce callus tissue culture experiments using completelyrandomized design (CRD) factorial. The first factor is the level of NAA treatment that is 0, 1,1.5, 2 and 3 mg/l. The second factor is the level of BAP treatment with 0, 0.5, 1, and 1.5mg/l. Each treatment was repeated 3 times; (2) Preparation of handouts from the research as asource of learning the ADDIE model (Analysis, Design, Development, Implementation, andEvaluation).Parameters measured were the percentage of growing explants, while appearingcallus and callus texture. Analysis of data growing percentage of explants with advancedANOVA and DMRT test at 5% level, while the current and emerging callus texturedescriptively. In a growing percentage of explants parameter combination treatment showed apercentage of 100 % are in treatment A 0 B 1,5 , A 1 B 0,5 - A 3 B 1,5 . For the current parametersappear callus treatment best combination found in treatment A 3 B 1,5 with a mean time of 2HSK appear callus (days after culture) and for the texture parameters of combinationtreatment showed callus crumb texture and white color found in treatment A 2 B 0,5 - A 3 B 1,5 , theresearch on callus growth can be used as a learning resource in the form of handouts for highschool level studentsKeywords : Handout, Tanaman Rosella, Kultur kalus, Hormon NAA dan BAP